THE EFFECT OF SYAHRUL LUGHAH PROGRAM PLANNING ON IMPROVING ARABIC LANGUAGE COMPETENCE OF UINSI SAMARINDA STUDENTS: (George R. Terry's Management Theory Perspective) - Romi Saputra; Safira Aulia; Durroh Marwa binti Mokmin; Nuril Mufidah (Lahjah Arabiyah : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
This study aims to describe the planning of the Syahrul Lughah Program at UINSI Samarinda and its influence on improving students’ Arabic language competence. The research focuses specifically on the planning aspect, as part of George R. Terry's management theory, which includes objectives, strategy, scheduling, and preliminary evaluation. This study uses a quantitative approach with descriptive and inferential statistical analysis. Data were collected through questionnaires distributed to 120 students who participated in the program. The findings show that the planning of the Syahrul Lughah Program was well-structured, with clear goals and relevant learning strategies. Statistical analysis indicates a significant influence between planning quality and the improvement of students’ Arabic proficiency, with a coefficient of determination (R²) of 37.4%. Among the planning components, objectives and strategy had the strongest contribution to the program’s success, while preliminary evaluation scored the lowest, indicating a lack of standardized assessment of participants' initial abilities. The study concludes that effective planning is a crucial determinant in the success of Arabic language programs. Strengthening the evaluation phase and refining the implementation schedule are recommended to maximize learning outcomes in similar intensive programs.